2022
DOI: 10.1097/corr.0000000000002484
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Health and Patients With Traumatic Injuries: Is There a Relationship Between Social Health and Orthopaedic Trauma?

Abstract: BackgroundAlthough economic stability, social context, and healthcare access are well-known social determinants of health associated with more challenging recovery after traumatic injury, little is known about how these factors differ by mechanism of injury. Our team sought to use the results of social determinants of health screenings to better understand the population that engaged with psychosocial support services after traumatic musculoskeletal injury and fill a gap in our understanding of patient-reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…An encouraging aspect of this month’s paper by Breslin et al [4] is their description of the work done by Trauma Recovery Services to identify and meet SDOH needs. Several other institutions have implemented similar programs.…”
Section: How Do We Get There?mentioning
confidence: 99%
See 2 more Smart Citations
“…An encouraging aspect of this month’s paper by Breslin et al [4] is their description of the work done by Trauma Recovery Services to identify and meet SDOH needs. Several other institutions have implemented similar programs.…”
Section: How Do We Get There?mentioning
confidence: 99%
“…Most of the orthopaedic research involving SDOH and health disparities focuses on access to care and outcomes data rather than examining injury patterns. In this issue of Clinical Orthopaedics and Related Research ®, Breslin et al [4] sought to describe a relationship between underlying SDOHs and traumatic musculoskeletal injury. Their institution, Case Western Reserve University, is home to Trauma Recovery Services, a psychosocial support program for patients admitted with traumatic injuries.…”
Section: Where Are We Now?mentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17] It has further been shown that individuals with adverse social circumstances and underlying mental illness are at elevated risk for protracted and poor recovery. [17][18][19][20] The reasons for this are numerous, including limited access to relevant services due to insufficient income or insurance. 14,21 Most hospital systems, even in developed countries, lack routine access to screening and treatment for mental and social health needs.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature has demonstrated that assessment and management of mental health and social circumstances are essential to optimizing recovery. 17,18,[22][23][24][25] Programmes and measures in this space have not been standard of care, but have shown promise in improving patient engagement and mitigating early complications, readmissions, and trauma recidivism. 24,[26][27][28][29][30] This review will highlight the importance of mental health and social support programming in optimizing outcomes after acute traumatic injury.…”
Section: Introductionmentioning
confidence: 99%